Current gender preference of female students from two co-educational universities who had homosexual relationships in high school - Recto, Mara Kristina Orosa (UP College of Home Economics, 2012)
As stated in the interviews conducted by the Kinsey team, gender preference for romantic relationships towards the same or opposite gender is not always consistent across time. Thus, this study aims to determine 1) the affirmation or change in gender preference for romantic relationship among female co-educational university students who had homosexual relationship in an exclusive girls in high school, 2) the factors that contributed to the respondent's gender preference from high school to college, and 3) their perception of acceptance of their respective families and members of their household. Thirty respondents (30) were purposively sampled through the snowball method from two selected universities. Fifteen (15) of the respondents are students from sectarian university and the other fifteen (15) are students from a non-sectarian university. The respondents were asked to answer a data profiling questionnaire for ten (10) minutes, consented for an interview, and were interviewed for thirty (30) to forty five (45) minutes. The researchers used descriptive statistics and Pearson's Chi Square test to analyze the data. The results show that the respondents changed and affirmed their gender preference for romantic relationship from high school to college. This data was strenghted by Erik Erikson's psychosocial stage theory of personality development. The factors that contributed to the affirmation and change of their gender preference are school environment, family, friends, religion, age, past and current relationship experience, etc. These factors are part of Urie Bronfenbrenner's Ecological Systems Theory. Lastly, the perception of the respondents' family on their gender preference for romantic relationship varies for every member of the family. In sum, gender is fluid and changes overtime. Each individual should be given the opportunity to freely explore their gender preference for for romantic relationship without the judgement of their immediate environment and society as well.